Effect of sugarcane biopolymer gel injected in rabbit vocal fold - Leão,Rodrigo Augusto de Souza (2014)
INTRODUCTION: Alterations in the vocal folds that involve volume reduction and glottal closure failure result in exaggerated air escape during speech. For such situations, the use of implants or grafts of different materials has been proposed. OBJECTIVE: To define the effect of sugarcane biopolymer gel when implanted in the vocal folds of rabbits. METHODS: This was an experimental study. The vocal folds of rabbits injected with sugarcane biopolymer and saline solution were histologically evaluated after 21 and 90 days. RESULTS: Mild to moderate inflammation and increased volume were observed in all vocal folds injected with biopolymer, when compared to controls. There were no cases of necrosis or calcification. DISCUSSION: This study showed higher inflammatory reaction in cases than in controls and biopolymer biointegration to the vocal fold. This fibrogenic response with absence of epithelial repercussions suggests that the biopolymer in its gel form can be bioactive and preserve the normal vibratory function of the epithelium. CONCLUSION: We show that in spite of producing an inflammatory reaction in vocal fold tissues, the material remained in vocal fold throughout the study period.